(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Fungal infections represent an increasing global health challenge due to the emergence of drug-resistant fungal pathogens and the limited availability of effective antifungal agents. Consequently, medicinal plants have gained significant attention as potential sources of novel bioactive compounds. Lantana camara L. (Verbenaceae) is a medicinal plant rich in phytochemicals with reported antimicrobial and antifungal properties, making it a promising candidate for lead compound discovery. The present study aimed to computationally evaluate six phytochemicals isolated from Lantana camara—Eugenol, Linalool, Carvacrol, Eucalyptol, Oleanolic acid, and Ursolic acid—for their drug-likeness, physicochemical characteristics, and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) profiles using the SwissADME and pkCSM in silico platforms. Canonical SMILES of all compounds were retrieved from PubChem and analyzed for Lipinski’s Rule of Five compliance, topological polar surface area (TPSA), consensus LogP, gastrointestinal absorption, blood–brain barrier permeability, bioavailability score, CYP450 inhibition, AMES mutagenicity, hepatotoxicity, skin sensitization, and other pharmacokinetic parameters. The results demonstrated that Eugenol, Linalool, Carvacrol, and Eucalyptol exhibited zero Lipinski violations, high gastrointestinal absorption, blood–brain barrier permeability, and favorable bioavailability scores of 0.55, along with low predicted toxicity. In contrast, Oleanolic acid and Ursolic acid showed one Lipinski violation due to high molecular weight (456.70 g/mol) and LogP values exceeding 7, resulting in lower gastrointestinal absorption. Among all compounds, Eugenol emerged as the most promising antifungal lead owing to its zero Rule-of-Five violations, low molecular weight (164.20 g/mol), TPSA of 29.46 Å², favorable ADMET profile, and well-documented antifungal mechanism. These findings support further molecular docking, in vitro antifungal evaluation, and nano formulation studies to validate Eugenol as a potential antifungal drug candidate.